Eksistensi Penggunaan Bahasa Indonesia Pada Era Globalisasi (Jurnal Ilmu Agama dan Pendidikan Agama Buddha, 2023)
Language is a human too for thinking which is the initia source of human understanding and knowledge, as a symbol of understanding, language has enabed humans to understand what is around them, and eads them to have knowledge and expertise. Globaization is an era of mass change due to the infuence of foreign cuture. Gobalization affects a aspects of ife, incuding language. An increasingy goba language used by a nations in the word is Engish, which uses more than one biion. As quoted from Kompas Onine which expains that English, for exampel, even though the user is getting bigger as a second anguage, the peope of a country wi be stronger and aso maintain their mother tongue: Language in gobaization era has an important roe, Indonesian peope is hoping to use Indonesian anguage as its function. Thought, gobaization era include in many aspects such as economy, technoogy and language. This artice discussed about the deveopment of Indonesian language, existe nce of in globaization ers and others.